2016
DOI: 10.1002/jcp.25292
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Sublethal and Transient Stress of the Endoplasmic Reticulum on the Mitochondrial Population

Abstract: Endoplasmic reticulum (ER) and mitochondria are not discrete intracellular organelles but establish close physical and functional interactions involved in several biological processes including mitochondrial bioenergetics, calcium homeostasis, lipid synthesis, and the regulation of apoptotic cell death pathways. As many cell types might face a transient and sublethal ER stress during their lifetime, it is thus likely that the adaptive UPR response might affect the mitochondrial population. The aim of this work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 128 publications
1
6
0
Order By: Relevance
“…The profound collapse of the maximal respiratory capacity in all cell lines upon artesunate treatment corresponds well with their decreased basal respiration and points to significant and irreversible damage to cell respiration. This is in line with previously reported mitochondrial fragmentation as a consequence of ER stress [ 27 ]. Further evidence for this hypothesis comes from the observation that artesunate affected increased cytotoxicity in GSH-depleted malignant cells, but not in normal B-cells.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The profound collapse of the maximal respiratory capacity in all cell lines upon artesunate treatment corresponds well with their decreased basal respiration and points to significant and irreversible damage to cell respiration. This is in line with previously reported mitochondrial fragmentation as a consequence of ER stress [ 27 ]. Further evidence for this hypothesis comes from the observation that artesunate affected increased cytotoxicity in GSH-depleted malignant cells, but not in normal B-cells.…”
Section: Discussionsupporting
confidence: 94%
“…Given the well-established close interaction between ER and mitochondria, stress signals induced in the ER may negatively influence a variety of mitochondrial metabolic functions [ 24 26 ]. It has previously been reported that induction of ER stress leads to fragmentation of the mitochondrial structure and a decrease in mitochondrial membrane potential, oxygen production, and reduced respiration [ 27 ]. The impact of artesunate on the metabolism was assessed using a seahorse metabolic analyzer (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Overload ER stress is considered to be an important regulator of several cellular pathological processes, including cancer cell death pathways in response to anticancer drugs. In addition, excessive ER stress can also affect the cell mitochondrial function, to further promote the occurrence of apoptosis (Finley, 2016;Vannuvel et al, 2016;Burton et al, 2016). Breast cancer is the most common cancer in women worldwide (Golubnitschaja et al, 2016;Chen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…During cell apoptosis process, abnormal alternations on oxidation system, mitochondrial function, and proapoptotic and antiapoptotic protein levels were observed [1012]. Mitochondria apoptosis, a well-known death signaling pathway, accompanies mitochondrial depolarization, cytochrome C (Cyt C) overrelease, and caspase-3 activation.…”
Section: Introductionmentioning
confidence: 99%